EFFECT OF IDLE TIME AND BERTHING TIME ON LOADING PRODUCTIVITY IN SURABAYA CONTAINER TERMINAL - Ivanhoe, Ivanhoe; Sumali, Bambang (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Improving loading and unloading efficiency at container terminals is a significant challenge in the maritime industry, with idle time and berthing time at the Container Terminal being key factors influencing loading productivity and potentially causing disruptions in the supply chain and reducing customer service quality. This study aims to determine the effect of idle time and Berthing time on loading and unloading productivity at the pier of the ocean-going container terminal Surabaya (TPS) Pelindo III." The strategy in research uses associative with a quantitative approach. The target population in this study were all employees and workers at the Surabaya container terminal, with a sample of 38 respondents. The sampling technique in this study used the Slovin technique. Sampling with the Accidental Sampling approach, the researcher takes a sample of the sampling technique based on coincidence. The type of data used is quantitative. Quantitative data in this study is data sourced directly from respondents presented in the form of a Likert scale. Data collection techniques are used by distributing questionnaires or questionnaires. The data statistical method used is descriptive statistics and Partial Least Square (PLS) with the SmartPLS version 4.0 program. The results of this study are that there is a positive and significant effect of idle time on loading and unloading productivity, and there is a positive and significant effect of berthing time on loading and unloading productivity; there is a positive and significant effect simultaneously of idle time and berthing time on purchasing decisions, idle time and Berthing time significantly affects the productivity of loading and unloading.